FPGA Based, Low Cost Modulators of BPSK and BFSK, Design and Comparison of Bit Error Rate over AWGN Channel - Soenmez, Mehmet; Akbal, Ayhan (Gazi Univ, 2013)
This paper presents the simulation results of binary frequency shift keying (BFSK) and binary phase shift keying (BPSK) modulation techniques in FPGA complier. Both modulation techniques are proposed in low power consumption systems. In addition, these modulation techniques are used high speed systems. Also, in this paper BPSK and BFSK modulations are compared to bit error rate (BER). BPSK modulation technique has BER low than BFSK modulation in AWGN channel. Thereby, as satellite communication for systems which need very high speed data transfer, BPSK modulation technique is preferred. For BPSK and BFSK modulation techniques, modulators were designed using FPGA complier (Quartus II 9.1). In Quartus II complier, results of simulation are observed using vector waveform file.
Keywords: FBGA; BPSK; BFSK; Modulator; AWGN; BER